2020
DOI: 10.3390/ijms21041279
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Doxorubicin-induced Systemic Inflammation: Implications for Hepatic Cytochrome P450 Regulation

Abstract: Doxorubicin (DOX) is an effective chemotherapeutic agent used to treat a wide variety of malignancies. In addition to its multi-organ toxicity, DOX treatment has been shown to induce systemic inflammation in patients and experimental animals. Inflammation alters the expression of hepatic cytochrome P450 (CYP) enzymes, which play important roles in drug metabolism and DOX-induced toxicity. Significant sex differences have been reported in DOX-induced toxicity; however, sex differences in DOX-induced systemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…Finally, we wanted to investigate the effects of DOX and the tumor on systemic inflammation. DOX itself has been shown in previous models to induce systemic inflammation [11,61]. However, the DOX regimen used in our study did not cause a significant increase in serum inflammatory markers in tumor-free mice.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Finally, we wanted to investigate the effects of DOX and the tumor on systemic inflammation. DOX itself has been shown in previous models to induce systemic inflammation [11,61]. However, the DOX regimen used in our study did not cause a significant increase in serum inflammatory markers in tumor-free mice.…”
Section: Discussioncontrasting
confidence: 55%
“…We have previously reported that acute DOX administration elicited a systemic inflammatory response in adult C57BL/6N mice [11]. Herein, we determined the effect of chronic DOX administration on serum levels of the inflammatory markers IL-6 and TNF-α, in juvenile tumor-free and tumor-bearing mice.…”
Section: Divergent Effects Of Dox On Serum Inflammatory Cytokines In Tumor-free Versus Tumor-bearing Micementioning
confidence: 95%
See 1 more Smart Citation
“…These ROS have been shown to induce CYP1B1 as well [173]. At last, DOX has been shown to provoke a strong inflammatory response which may lead to CYP1B1 induction, particularly through IL-6 and TNFα-mediated signaling [167,174]. Intriguingly, DOX-induced inflammation in the heart of C57Bl/6 mice was sexually dimorphic with stronger inflammatory response in hearts of male mice [19].…”
Section: Effect Of Anthracyclines On Cyp1b1 Expressionmentioning
confidence: 99%
“…Rodents (rats, mice) are genetically similar to humans, and are often used for experimental models of AKI. These animal studies have repeatedly suggested that sexual hormones (testosterone, testosterone/ estrogen ratio, estrogen) are important determinants of sex differences in AKI susceptibility [17][18][19][20][21][22][23]. Female rodents (mice, rats) are much more resistant to ischemic renal injury when compared with male rodents.…”
Section: Sex and Susceptibility Of Rodents To Experimental Aki Modelsmentioning
confidence: 99%